MicroRNAs, Major Players in B Cells Homeostasis and Function - Danger, Richard (Frontiers Media S.A., 2014)
As a main actor in humoral immunity, B cells participate in various antibody-related disorders. However, a deeper understanding of B-cell differentiation and function is needed in order to decipher their immune-modulatory roles, notably with the recent highlighting of regulatory B cells. microRNAs (miRNAs), key factors in various biological and pathological processes, have been shown to be essential for B-cell homeostasis, and therefore understanding their participation in B-cell biology could help identify biomarkers and contribute toward curing B-cell-related immune disorders. This review aims to report studies casting light on the roles played by miRNAs in B-cell lineage and function and B-cell-related immune pathologies.